Neuroprotective effects of ultra-high dose rate FLASH Bragg peak proton irradiation - Dokić, Ivana; Meister, Sarah; Bojcevski, Jovana; Tessonnier, Thomas; Walsh, Dietrich; Knoll, Maximilian; Mein, Stewart; Tang, Zili; Vogelbacher, Lena; Rittmüller, Claudia; Moustafa, Mahmoud; Krunic, Damir; et al. (International journal of radiation oncology, biology, physics, 2022)
Purpose - To investigate brain tissue response to ultra-high dose rate (uHDR, FLASH) and standard dose rate (SDR) proton irradiations in the Bragg peak region. - Methods and Materials - Active scanning uHDR delivery was established for proton beams for investigation of dose rate effects between clinical SDR and uHDR at ∼10 Gy in the Bragg peak region (dose-averaged linear energy transfer [LETD] ranging from 4.5 to 10.2 keV µm-1 ). Radiation- induced injury of neuronal tissue was assessed by studying the DNA double strand break repair kinetics surrogated by nuclear γH2AX staining (radiation induced foci [RIF]), microvascular density and structural integrity (MVD, CD31+ endothelium), and inflammatory microenvironmental response (CD68+ microglia/macrophages and high mobility group box protein 1[HMGB]) in healthy C57BL/6 mouse brains. - Results - Averaged dose rates achieved were 0.17 Gy/s (SDR) and 120 Gy/s (uHDR). The fraction of RIF-positive cells increased after SDR ∼10-fold, whereas a significantly lower fraction of RIF-positive cells was found after uHDR versus SDR (∼2 fold, P < .0001). Moreover, uHDR substantially preserved the microvascular architecture and reduced microglia/macrophage regulated associated inflammation as compared with SDR. - Conclusions - The feasibility of uHDR raster scanning proton irradiation is demonstrated to elicit FLASH sparing neuroprotective effects compared to SDR in a preclinical in vivo model.
Gesehen am 17.09.2022